Responsive Vagus Nerve Stimulation for Drug Resistant Epilepsy: A Review of New Features and Practical Guidance for Advanced Practice Providers - Fisher, Breanne; DesMarteau, Julie A.; Koontz, Elizabeth H.; Wilks, Seth J.; Melamed, Susan E. (Frontiers in Neurology, 2021)
Vagus nerve stimulation (VNS) is a safe and effective therapy that has been available for over 20 years for adults and children with drug resistant epilepsy (DRE). Since U.S. Food and Drug Administration approval in 1997, VNS has been implanted in over 100,000 patients including over 30,000 children as an adjunctive therapy in reducing the frequency of seizures in patients four years of age and older with focal seizures that are refractory to antiseizure medications. VNS Therapy® has evolved over time and currently offers closed-loop, responsive stimulation as well as advanced features that streamline dosing and patient management. Advanced Practice Providers (APPs) such as nurse practitioners, physician assistants and clinical nurse specialists are integral in a comprehensive healthcare team, and dedicated VNS clinics have formed at comprehensive epilepsy centers across the world that are often managed by APPs. This approach improves access, education, and continuity of care for those with VNS or those considering VNS. Here we provide a review for APPs on the VNS Therapy® system focused on new features, dosing, and troubleshooting strategies with the goal to provide guidance to those managing VNS patients.